2015
DOI: 10.1038/jcbfm.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated pericyte degeneration and blood–brain barrier breakdown in apolipoprotein E4 carriers with Alzheimer’s disease

Abstract: The blood-brain barrier (BBB) limits the entry of neurotoxic blood-derived products and cells into the brain that is required for normal neuronal functioning and information processing. Pericytes maintain the integrity of the BBB and degenerate in Alzheimer's disease (AD). The BBB is damaged in AD, particularly in individuals carrying apolipoprotein E4 (APOE4) gene, which is a major genetic risk factor for late-onset AD. The mechanisms underlying the BBB breakdown in AD remain, however, elusive. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
478
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(523 citation statements)
references
References 42 publications
19
478
4
2
Order By: Relevance
“…The increase in vascular permeability in these mice was linked to a decrease in apoE-dependent pericyte-expressed LRP1 activation and a concomitant increase in CypA-MMP9 activity. In support of these findings, a human study using postmortem brain samples from control and AD subjects found accelerated pericyte degeneration in AD APOE-4 carriers compared with AD APOE-3 carriers and non-AD controls (126). Intriguingly, a significant increase in CypA and MMP-9 was also detected in pericytes and endothelial cells of APOE-4 subjects relative to APOE-3 subjects.…”
Section: Apoe and A Clearancementioning
confidence: 71%
“…The increase in vascular permeability in these mice was linked to a decrease in apoE-dependent pericyte-expressed LRP1 activation and a concomitant increase in CypA-MMP9 activity. In support of these findings, a human study using postmortem brain samples from control and AD subjects found accelerated pericyte degeneration in AD APOE-4 carriers compared with AD APOE-3 carriers and non-AD controls (126). Intriguingly, a significant increase in CypA and MMP-9 was also detected in pericytes and endothelial cells of APOE-4 subjects relative to APOE-3 subjects.…”
Section: Apoe and A Clearancementioning
confidence: 71%
“…35 In humans, cognitively healthy APOEε4 carriers showed higher age-dependent blood-brain barrier breakdown than APOEε3 carriers, 36 and whereas in patients with AD both APOEε4 and APOEε3 carriers had more pericyte degeneration than in healthy controls, the difference was most profound in the former. 37 In addition, in a large memory clinic cohort, amyloid deposition in those with small vessel disease was most aggravated in APOEε4 carriers. 30 Associations between vasoreactivity and dementia remained similar overall, and became stronger for APOEε4 carriers after adjustment for traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis replicates this phenomenon, as CT pathology was the driver of decreased cognitive performance following mTBI, with greater deleterious associations with consolidation and retrieval rather than encoding. This supports the idea that following ischemia and neuronal damage, the reduced antioxidant and biological activity of the ε 4 allele may exacerbate vascular endothelial injury (Bell et al., 2012; Halliday et al., 2016) and lead to cognitive deficits (Friedman et al., 1999). Similar results have been described in AD patients with left temporal and/or hippocampal damage, where a subtle decline in episodic memory occurs prior to the emergence of full dementia.…”
Section: Discussionmentioning
confidence: 99%